Omnibus Law : Dalam Perspektif Hukum Responsif - Pudjo Utomo (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2019)
One of the problems with investing in Indonesia is legal certainty in the field of licensing. The number of overlapping regulations, and bad services, have an impact on the lack of investor interest. Therefore it is necessary to regulate investment regulations and legal systems. This research is analytical descriptive with normative juridical approach. This study finds legislation related problems and synchronization problems, with reference to the concept of responsive law. It was concluded, the need to formulate a model of law that could bridge and at the same time resolve regulatory issues with the establishment of the Omnibus Law / Omnibus Law.Salah satu masalah berinvestasi di Indonesia adalah kepastian hukum bidang perizinan. Jumlah peraturan yang tumpang tindih, dan pelayanan buruk, berdampak pada kurangnya minat investor. Oleh karena itu perlu untuk mengatur peraturan dan sistem hukum investasi. Penelitian ini bersifat deskriptif analitis dengan pendekatan yuridis normatif. Studi ini menemukan masalah legislasi terkait dan masalah sinkronisasi, dengan merujuk pada konsep hukum responsif. Disimpulkan, perlunya merumuskan model undang-undang yang bisa menjembatani dan sekaligus menyelesaikan masalah regulasi dengan pembentukan Undang-Undang Omnibus/ Omnibus Law.